Systemic risk-taking: amplification effects, externalities, and regulatory responses - Anton Korinek (European Central Bank (ECB), 2011)
This paper analyzes the efficiency of risk-taking decisions in an economy that is prone to systemic risk, captured by financial amplification effects that occur in response to strong adverse shocks. It shows that decentralized agents who have unconstrained access to a complete set of Arrow securities choose to expose themselves to such risk to a socially inefficient extent because of pecuniary externalities that are triggered during financial amplification. The paper develops an externality pricing kernel that quantifies the state-contingent magnitude of such externalities and provides welfaretheoretic foundations for macro-prudential policy measures to correct the distortion. Furthermore, it derives conditions under which agents employ ex-ante risk markets to fully undo any expected government bailout. Finally, it finds that constrained market participants face socially insufficient incentives to raise more capital during episodes of financial amplification.
Keywords: E44; G13; G18; D62; H23; 330; bailout neutrality; externality pricing kernel; financial amplification; macroprudential regulation; systemic externalities; systemic risk